1998
DOI: 10.1074/jbc.273.25.15866
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Basis for the Absence ofN-Glycolylneuraminic Acid in Humans

Abstract: N-Glycolylneuraminic acid (NeuGc) is abundantly expressed in most mammals, but it is not detectable in humans. The expression of NeuGc is controlled by cytidine monophospho-N-acetylneuraminic acid (CMPNeuAc) hydroxylase activity. We previously cloned a cDNA for mouse CMP-NeuAc hydroxylase and found that the human genome contains a homologue. We report here the molecular basis for the absence of NeuGc in humans. We cloned a cDNA for human CMP-NeuAc hydroxylase from a HeLa cell cDNA library. The cDNA encodes a 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
321
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 377 publications
(328 citation statements)
references
References 36 publications
5
321
0
2
Order By: Relevance
“…Recently, however, it was shown that N-glycolylation of sialic acid by CMP-NeuAc hydroxylase significantly affects CD22 ligand activity in murine system, as glycans carrying NeuGc␣2-6 termini are much preferred ligands for murine CD22 compared with glycans carrying NeuAc␣2-6 termini (16). Because humans have no NeuGc due to deletion of exons in the CMP-NeuAc hydroxylase gene (37,38), this regulatory mechanism is not applicable to humans. Instead, our results suggest a role for 6-O-sulfotransferases, which are known to be affected by various stimuli and depend on cellular activation status (34, 39 -41), in the regulation of CD22 ligand activity, as well as ␣2-6-sialyltransferases.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, however, it was shown that N-glycolylation of sialic acid by CMP-NeuAc hydroxylase significantly affects CD22 ligand activity in murine system, as glycans carrying NeuGc␣2-6 termini are much preferred ligands for murine CD22 compared with glycans carrying NeuAc␣2-6 termini (16). Because humans have no NeuGc due to deletion of exons in the CMP-NeuAc hydroxylase gene (37,38), this regulatory mechanism is not applicable to humans. Instead, our results suggest a role for 6-O-sulfotransferases, which are known to be affected by various stimuli and depend on cellular activation status (34, 39 -41), in the regulation of CD22 ligand activity, as well as ␣2-6-sialyltransferases.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, humans generate immune responses against i.v.-administered molecules carrying Neu5Gc, e.g., the ''serum sickness'' reaction to equine antithymocyte globulin therapy (9,10). These findings are explained by a human-specific inactivating mutation in the CMAH gene (11)(12)(13)) that occurred Ϸ2.5 million to 3 million years ago (14).…”
mentioning
confidence: 97%
“…The suppression of Neu5Gc is most conspicuous in humans in that there is no detectable level of Neu5Gc in almost all tissues (Muchmore et al 1998). This was explained by the finding that the human CMAH locus is genetically inactivated despite the fact that it is a single-copy gene located on 6p21 (Chou et al 1998;Irie et al 1998), and it has been suggested that this defective mutation might be responsible for some biochemical or physiological characteristics specific to humans (Varki 2002). …”
mentioning
confidence: 99%